Hemorheological and cardiovascular effects of erythropoietin in a rat model of sports doping - Piloto, N. (2011)
Recombinant human erythropoietin (rhEPO) has been therapeutically used for correction of anaemia. However, due to the increase in circulating red blood cells (RBCs) it promotes, thus increasing oxygen delivery to muscles and improving performance in sport, it has been also illegally used as sports doping. Besides the well known increase of hematocrit and blood viscosity; which might cause serious complications for the athletes, other disturbances could occur, whose mechanisms remain to be fully elucidated. This study aimed to evaluate the hemorheological and cardiovascular effects of administration of rhEPO to rats under chronic aerobic exercise. A ten week-protocol was performed in four male Wistar rat groups: control — sedentary; rhEPO — 50 IV/kg, 3 times/wk; exercised (EX) — swimming for 1 hr, 3 times/ wk; EX+rhEPO. rhEPO in trained rats promoted erythrocyte count increase, hypertension, heart hypertro-phy, sympathetic and serotonergic overactivation, as well as a trend to increased oxidative stress. In conclusion, rhEPO doping in rats under chronic exercise promotes not only the expected increased hematocrit, but also other serious deleterious cardiovascular and thromboembolic modifications, including live risk, which might be known and assumed by all sports authorities, including athletes and their physicians.